Are adenoma and serrated polyp detection rates correlated with endoscopists’ sensitivity of optical diagnosis? - Bronzwaer, Maxime E. S.; Vleugels, Jasper L. A.; van Doorn, Sascha C.; Dijkgraaf, Marcel G. W.; Fockens, Paul; Dekker, Evelien; on behalf of the DISCOUNT-2 study group (Endoscopy, 2020)
Introduction Endoscopists with a high adenoma detection rate (ADR) and proximal serrated polyp detection rate (PSPDR) detect these polyps more frequently, which may be attributable to better recognition of their endoscopic features. Little is known about the association between endoscopic lesion detection and differentiation skills. Therefore, we evaluated the correlation between the ADR, PSPDR, and the sensitivity of optical diagnosis for adenomas and serrated polyps. Methods We performed an exploratory post-hoc analysis of the DISCOUNT-2 study, including complete colonoscopies after a positive fecal immunochemical test (FIT) performed by endoscopists who performed ≥ 50 colonoscopies. The correlations between the ADR, PSPDR, and the sensitivity of optical diagnosis were calculated using Pearson’s rho correlation coefficient.Results 24 endoscopists performed ≥ 50 colonoscopies, resulting in a total of 2889 colonoscopies. The overall ADR was 84.5 % (range 71.4 % – 95.3 %) and overall PSPDR was 13.7 % (4.3 % – 29.0 %). The sensitivity of optical diagnosis for adenomas and serrated polyps were 94.5 % (83.3 % – 100 %) and 74.0 % (37.5 % – 94.1 %), respectively. No correlation could be demonstrated between the ADR and the sensitivity of optical diagnosis for adenomas (−0.20; P = 0.35) or between the PSPDR and the sensitivity of optical diagnosis for serrated polyps (−0.12; P = 0.57).Conclusions In a homogeneous FIT-positive population, no correlation between the ADR, PSPDR, and the sensitivity of optical diagnosis for adenomas and serrated polyps could be demonstrated. These exploratory results suggest that lesion detection and differentiation require different endoscopic skills. Further prospective studies are needed; until then, monitoring of both performance indicators is important to secure optimal efficacy of FIT-based colorectal cancer screening.